Brief Psychometric Analysis of the Self-Evaluation Scale–Parent Report (SES–P). (3rd July 2017) - Bardhoshi, Gerta; Erford, Bradley T.; Sherman, Martin F.; Atalay, Zumra
ABSTRACT: The Self-Evaluation Scale–Parent Report (SES–P) assesses parents' perceptions of the self-concept of their children aged 7 to 17 years. Internal aspects of validity indicated a marginal to adequate fit of the data to both the unidimensional and hypothesized 4-factor model. The SES–P had excellent convergent and discriminant validity.